2020
DOI: 10.1155/2020/5386960
|View full text |Cite
|
Sign up to set email alerts
|

Robust Stabilization of Nonlinear Fractional Order Interconnected Systems Based on T-S Fuzzy Model

Abstract: This paper concerns robust stabilization of nonlinear fractional order interconnected systems. Based on uncertain fractional order Takagi–Sugeno fuzzy model and the fractional order extension of lyapunov direct method, a parallel distributed compensate controller is designed to asymptotically stabilize the fractional order interconnected systems. Then, a sufficient condition is given in the format of linear matrix inequalities. Simulation example is given to validate the effectiveness of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Yang et al [35] used different samples to train a T-S fuzzy neural network, and the results showed that the composition and quantity of training samples had an important impact on water quality evaluation. Li [36] used a T-S fuzzy neural network to study the robust stabilization of nonlinear fractional-order interconnected systems. Song et al [37] focused on the state estimation issue of T-S fuzzy Markovian generalized neural networks with reaction-diffusion terms.…”
Section: Application Of T-s Fuzzy Neural Network In Other Fieldsmentioning
confidence: 99%
“…Yang et al [35] used different samples to train a T-S fuzzy neural network, and the results showed that the composition and quantity of training samples had an important impact on water quality evaluation. Li [36] used a T-S fuzzy neural network to study the robust stabilization of nonlinear fractional-order interconnected systems. Song et al [37] focused on the state estimation issue of T-S fuzzy Markovian generalized neural networks with reaction-diffusion terms.…”
Section: Application Of T-s Fuzzy Neural Network In Other Fieldsmentioning
confidence: 99%